MODEL PENERAPAN KEPEMIMPINAN STRATEGIS UNTUK MENCIPTAKAN KEUNGGULAN BERSAING PADA BENGKEL PERAWATAN DAN PERBAIKAN TOYOTA PT. HADJI KALLA CABANG URIP SUMOHARJO MAKASSAR - Nashriah Akil (Jurnal Bisnis dan Kewirausahaan, 2016)
This study aims to determine the strategic leadership model that is applied in order to create a competitive advantage in the Maintenance and Repair Shop Toyota PT. Hadji Kalla Branch Urip Sumoharjo. This study used qualitative methods, more emphasis on qualitative descriptive type of approach that identify and describe the strategic leadership that is applied Repair Maintenance and Repair Toyota PT. Hadji Kalla Urip to create competitive advantage. From the results of this study concluded that the strategic leadership BPP Toyota PT. Hadji Kalla Urip very well marked throughout all levels of business strategy (corporate level, bussiness level, & funcional level) plays a role determining strategic direction, competence mainstay owned consists of kaizen, standard services TSA21, Maintenance Remainder System, Quality Control, the customer is a friend, Toyota production sytem. Forms of Human Resources Development is for technicians follow a tiered training, employee benefits and career development. Effective organizational culture is thick, namely family, our faith, our company is a mandatory exercise routine. For a company that is ethical practice listening skills, speaking, friendly and courteous as well as respect and caring. While the company's organizational control through discipline supervision and evaluation of the meeting. Possessed of strategic leadership, the company needs to maintain and further enhanced. But keep attention on supporting the development of staff that they lack the opportunities and customer engagement to support the company culture